Effect of gold nanoparticles in titanium oxide layer on the photovoltaic performance of inverted-type organic thin-film solar cells. (13th August 2017) - Akiyama, Tsuyoshi; Sakata, Hiroki; Matsumoto, Taisuke; Mitsukawa, Shota; Sakaguchi, Hiroshi; Oku, Takeo
ABSTRACT: Gold nanoparticle/titanium oxide composite materials were prepared at low temperature and were used as electron-transport layers for inverted-type organic thin-film solar cells. The application of gold nanoparticle/titanium oxide composite materials led to an improvement in the photoelectric conversion efficiency of the solar cells under simulated sunlight irradiation.